Factors affecting the quality of training and development provided to non-physician healthcare professionals: a scoping review - Alshraa, Alaa; Abdul Manaf, Rosliza; Mahmud, Aidalina (AME Publishing Company, 2024)
Background: Human resources are regarded as one of healthcare systems’ most valuable assets and an essential building block. The availability of well-trained and competent healthcare professionals is critical, strategic, and tightly linked to training and development (T&D). Meanwhile, quality T&D has been, and remains, a fundamental aspect of the health workforce development and growth, which aids institutions in running effectively and efficiently, according to the highest standards. This review sought to identify the key factors and elements that affect the quality of T&D provided to non-physician healthcare professionals. Methods: A scoping review using the updated Joanna Briggs Institute (JBI) methodological framework was conducted to identify and synthesize the published research and gray literature. A holistic search was performed using the following electronic databases: ScienceDirect, MEDLINE, CINAHL, and Google Scholar. Evidence sources in any geographical area, in English, full-text, and published between 1990–2022 that fulfilled the inclusion and exclusion criteria were included. Results: Forty sources were included, exploring various factors and elements that affect the quality of T&D provided to non-physician healthcare professionals. Twenty-one empirical sources, twelve reviews, and seven gray literature sources were identified. Results on quality factors were categorized into (I) T&D process factors; (II) T&D system factors; (III) work environment factors; and (IV) healthcare professional factors. Conclusions: In the current changing environment, healthcare institutions need to invest in and nurture their healthcare professionals’ knowledge, skills, and abilities through high-quality T&D. In this review, several process, system, organizational, and personal factors affect the quality of T&D provided to nonphysician healthcare professionals, which are crucial to optimizing outcomes and meeting expectations. Accordingly, awareness of these factors will provide robust guidance to transform and modify how T&D initiatives and opportunities are planned, delivered, and evaluated.